The impact of combined oral contraceptives containing ethinyl estradiol and drospirenone on whole blood clot viscoelasticity and the biophysical and biochemical characteristics of erythrocytes - Swanepoel, A.C. (2026)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2018.